(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2024)
Oil palm cultivation and the conversion of tropical forests to pastures are impacting freshwater tropical systems. This study examines periphyton biomass, richness, diversity, and community composition in streams affected by forests, pastures, and oil palm plantations, with and without forest buffer strips. Streams shaded by forests or riparian buffers exhibited more canopy cover, lower water temperatures, and reduced light, while those in pastures and unbuffered plantations had higher periphyton biomass, indicated by elevated chlorophyll-a levels. Periphyton richness and diversity were higher in pasture streams compared to forested ones and streams through oil palm areas. Common periphyton taxa differed among stream depending of land cover. Streams in buffered and unbuffered palm plantations featured taxa such as Navicula and Gyrosigma, whereas pasture streams commonly included were characterized by genera such as Cymbella, and Gonatozygon, and forest stream communities featured Phormidium and Eunotia. Pasture streams displayed altered taxa richness and diversity compared to the other land uses. There were no significant differences in periphyton communities between the two oil palm cultivation types, indicating that conservation buffers may not effectively protect periphyton communities in these settings. This research highlights the need for further studies on the impacts of agricultural practices on aquatic primary producers.